The Promotion of Esports Image to the People in Thailand - Muendech, Sakkarin; Noriya, Wanchalee (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The purposes of this research were to 1) to study the level of public perception of esports images 2) to compare the level of public perception of esports images in each generation and 3) to study ways to promote the image of esports in Thailand. The researcher used mixed-method research. By using questionnaires to collect quantitative data from 4 generations of Thai citizens who playing esports games, watching games or esports competition 400 samples. And use in-depth interviews to collect qualitative data from key informants who are related or who have stakeholders, experienced and proficient in esports, both public sectors, private sectors, and citizens 10 persons. Statistics used to analyze quantitative data include: frequency, percentage, average, standard deviations, The one-way analysis of variance (ANOVA) and Scheffe’s method tests. Statistics used to analyze qualitative data include: content analysis and interpretation. The research found that 4 generations of Thai citizens who playing esports games, watching games or esports competition have a high level of awareness of the esports image, and the perception of the esports image differs at the statistical significance level of 0.05. Guidelines for promoting the image of esports to the people in Thailand include: Presenting the positive impact on the body of esports gaming, Presenting practical ways to reduce the negative impact on the body, Creating a sports idol, Presenting news about value or revenue from the esports industry, Publicizing knowledge about esports to the public, Organizing ongoing training and seminars to educate the public, Building knowledge and understanding for parents, and Creating a practice for parents to supervise their children.